The effect of iron deficiency anemia on the levels of hemoglobin subtypes: HbA1c, HbA2 and HbF before and after treatment - Akarsu, Saadet; Kurt, Abdullah; Cakici, Oya; Kurt, A. Nese Citak; Sengul, Ismail; Sen, Yasar (Aves, 2008)
Aim: There are some known factors that have effects on hemoglobin subtypes. There are varied results previously reported, about effects of iron deficiency anemia (IDA) on Hb subtypes at adult age. It was aimed to investigate the status of this effect the at pediatric age group. Material and Method: A total of 48 children with IDA were involved in the study. Changes in pre-and post-treatment levels of hemoglobin subtypes were investigated. Results: Mean age of the participants was 48.6 months. Of the cases 15 were females and 33 were males. Pre-treatment levels were as follows: of Hb 9.7 g/dl, MCV 67.7 fl, RDW % 17.8, serum iron (Fe) 28.6 mu mol/L, total iron binding capacity (TIBC) 340.5 mu g/dL, ferritin (F) 14.9 mu g/L, HbA1c 4.7 +/- 0.9%, HbA2 2.2 +/- 0.6% and HbF 4.4 +/- 0.2%. Post-treatment levels were as follows: Hb 12.6 g/dl, MCV 80.6 fl, RDW 13.9%, serum Fe 69.8 mu mol/L, TIBC 285.6 mu g/dL, F 40.9 mu g/L, HbA1c 4.7 +/- 0.8%, HbA2: 2.6 +/- 0.5% and HbF 8 +/- 0.5%. There was no significant difference between pre- d post- treatment levels of HbA1 and HbA1c. But pre-and post treatment levels of HbA2 and HbF were significantly different (p<0.05). Conclusions: IDA has effects on diagnosis and treatment criteria with HbA2 levels while not effective on such criteria with HbA1c levels. Because of cases' age, statistically significant reduction at HbF levels of our cases, is accepted as a normal physiologic process. Nevertheless, it is needed to carry out larger studies.
Demir eksikli?i anemisinin hemoglobin alt tipleri üzerine etkisi: Tedavi öncesi ve sonrasi HbA1c, HbA2 ve HbF
Keywords: HbA1c; HbA2; HbF; Iron deficiency anemia